EFEKTIVITAS TEKNIK SELF-TALK DALAM PENDEKATAN KONSELING KOGNITIF UNTUK MENINGKATKAN DISIPLIN DIRI PESERTA DIDIK - Diswantika, Noviana (LPPM STKIP PGRI Bandar Lampung, 2016)
This study aims to test the effectiveness of counseling through self-talk techniques to improve learners‟ self-discipline. Research approach used in this study was quantitative with quasi experimental method and nonequivalent pretest-posttest control group research design. Research subjects in this research is the students of X grade at SMK PGRI 2 Bandar Lampung which were determined using purposive sampling technique. Data were analyzed using the size of the central symptoms and paired t-test. The main research instruments was in the form of Self-Discipline of Students Scale. Interventions designed based on self-discipline general profile of learners and the data pre-test results. The results showed: (1) the level of self-discipline of students of X grade at SMK PGRI 2 Bandar Lampung are heading higher category; (2) the level of self-discipline of students of X grade at SMK PGRI 2 Bandar Lampung on five aspects show a tendency of highest level of self-discipline is the aspect of perseverance; (3)) empirically, counseling through self-talk technique effective for improving self-discipline of students of X grade at SMK PGRI 2 Bandar Lampung; (4) The increasing of the average score shows most indicated by the fourth aspect that is the ability to implement the decisions or plans after receiving treatments.